PROPERTIES OF RIGID PVC SHUTTER REINFORCED WITH GLASS FIBER - Roman, Krisztina; Roman, Laszlo (International Journal of Research -GRANTHAALAYAH, 2018)
In this paper the PVC shutter with glass fiber composite mechanical properties can be examined. Based on previous researches the shutter needs more additives to give higher stability to the UV irradiation and degradation. These effect (degradation) are the main problems for these shading industry areas. The relationship between the structure and the additives of the rigid PVC were investigated. With the mechanical tests, such as tensile-, bending-, impact- and hardness test the structural of the composite can be determined. The composites properties compared to a simple rigid PVC property. In the results of the mechanical tests, the ultimate strength and the belonging deformation were decreased compared to the simple PVC properties.